2015
DOI: 10.1038/srep11380
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of the gene defect responsible for severe hypercholesterolaemia using whole-exome sequencing

Abstract: Familial hypercholesterolaemia (FH) is a serious genetic metabolic disease. We identified a specific family in which the proband had typical homozygous phenotype of FH, but couldn’t detect any mutations in usual pathogenic genes using traditional sequencing. This study is the first attempt to use whole exome sequencing (WES) to identify the pathogenic genes in Chinese FH. The routine examinations were performed on all parentage members, and WES on 5 members. We used bioinformatics methods to splice and filter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Our group later conducted touch-down PCR together with DNA sequencing and denaturing high-performance liquid chromatography (DHPLC) to detect LDLR mutations 6 43 . We also conducted the first study to utilize an SNP-based genome-wide linkage scan and whole/targeted exome sequencing technologies to detect LDLR mutations in China 8 10 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Our group later conducted touch-down PCR together with DNA sequencing and denaturing high-performance liquid chromatography (DHPLC) to detect LDLR mutations 6 43 . We also conducted the first study to utilize an SNP-based genome-wide linkage scan and whole/targeted exome sequencing technologies to detect LDLR mutations in China 8 10 44 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 27 mutations in LDLR gene were identified (Table S1). There was no mutation found by DNA resequencing array in proband 11, even though a c.1187–10 G>A mutation was detected by the whole-exome sequencing method in a previous study11. In the DNA array group, a total of 16 mutations were identified across the 12 probands tested with DNA array.…”
Section: Resultsmentioning
confidence: 74%
“…Therefore, there is a pressing clinical incentive to develop effective screening methods420 for the early detection of FH. In a previous study, we used whole exome sequencing and TES to identify patients with HoFH and found that these technologies are useful for providing an accurate genetic diagnosis in patients with severe hypercholesterolemia1011. In the present work, we have analyzed 20 young patients with severe hypercholesterolemia by either array sequencing or TES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods of DNA extraction and sequencing have been reported in our previous studies. 4 The homozygous mutation in LDLR exon9 c.1187-10G>A, a 3' splice acceptor mutation in poly-pyrimidine tract of intron 8, was detected in the child and the heterozygous form was detected in his mother.…”
Section: Case Reportmentioning
confidence: 98%